Formation and optical properties of mixed multi-layered heterostructures based on all two-dimensional materials - Sheng, Y (2017)
The production of large area, high quality two-dimensional (2D) materials using chemical vapour deposition (CVD) has been an important and difficult topic in contemporary materials science research, after the discovery of the diverse and extraordinary properties exhibited by these materials. This thesis mainly focuses on the CVD synthesis of two 2D materials; bilayer graphene and monolayer tungsten disulphide (WS2). Various factors influencing the growth of each material were studied in order to understand how they affect the quality, uniformity, and size of the 2D films produced. Following this, these materials were combined to fabricate 2D vertical heterostructures, which were then spectroscopically examined and characterised. By conducting ambient pressure CVD growth with a flat support, it was found that high uniform bilayer graphene could be grown on the centimetre scale. The flat support provides for the consistent delivery of precursor to the copper catalyst for graphene growth. These results provide important insights not only into the upscaling of CVD methods for growing large area, high quality graphene and but also in how to transfer the product onto flexible substrates for potential applications as a transparent conducting electrode. Monolayer WS2 is of interest for use in optoelectronic devices due to its direct bandgap and high photoluminescence (PL) intensity. This thesis shows how the controlled addition of hydrogen into the CVD growth of WS2 can lead to separately distributed domains or centimetre scale continuous monolayer films at ambient pressure without the need for seed molecules, specially prepared substrates or low pressure vacuum systems. This CVD reaction is simple and efficient, ideal for mass-production of large area monolayer WS2. Subsequent studies showed that hexagonal domains of monolayer WS2 can have discrete segmentation in their PL emission intensity, forming symmetric patterns with alternating bright and dark regions. Analysis of the PL spectra shows differences in the exciton to trion ratio, indicating variations in the exciton recombination dynamics. These results provide important insights into the spatially varying properties of these CVD-grown TMDs materials, which may be important for their effective implementation in fast photo sensors and optical switches. Finally, by introducing a novel non-aqueous transfer method, it was possible to create vertical stacks of mixed 2D layers containing a strained monolayer of WS2, boron nitride, and graphene. Stronger interactions between WS2 on graphene was found when swapping water for IPA, likely resulting from reduced contamination between the layers associated with aqueous impurities. This transfer method is suitable for layer by layer control of 2D material vertical stacks and is shown to be possible for all CVD grown samples, a result which opens up pathways for the rapid large scale fabrication of vertical heterostructure systems with large area coverage and controllable thickness on the atomic level.